2022
DOI: 10.1039/d2ra04759d
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Fe3O4@boehmite NPs as efficient and magnetically recoverable nanocatalyst in the homoselective synthesis of tetrazoles

Abstract: Magnetic boehmite nanoparticles were synthesized from a hybrid of boehmite and Fe3O4 nanoparticles. Then, it was applied as a homoselective, highly efficient, cheep, heterogeneous and recoverable nanocatalyst in the synthesis of tetrazole derivative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 65 publications
(79 reference statements)
0
22
0
Order By: Relevance
“…Unfortunately, Fe 3 O 4 magnetic nanoparticles have lower surface area and lower stability. [16][17][18][19][20] Therefore, a nanocomposite of both MCM-41 and Fe 3 O 4 magnetic nanoparticles is great interest for various applications, especially in the field of catalysis, because MCM-41 MNC has advantages of both mesoporous MCM-41 and Fe 3 O 4 magnetic nanoparticles. [4,21] Therefore, MCM-41 MNC, which is formed from magnetic core surrounding by a mesoporous shell, has been used in the preparation of magnetically recyclable nanocatalysts due to its unique properties such as stable in different chemical reaction conditions, high stability, high-specific surface area, and ability to modify its surface, insolubility, and recoverability.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, Fe 3 O 4 magnetic nanoparticles have lower surface area and lower stability. [16][17][18][19][20] Therefore, a nanocomposite of both MCM-41 and Fe 3 O 4 magnetic nanoparticles is great interest for various applications, especially in the field of catalysis, because MCM-41 MNC has advantages of both mesoporous MCM-41 and Fe 3 O 4 magnetic nanoparticles. [4,21] Therefore, MCM-41 MNC, which is formed from magnetic core surrounding by a mesoporous shell, has been used in the preparation of magnetically recyclable nanocatalysts due to its unique properties such as stable in different chemical reaction conditions, high stability, high-specific surface area, and ability to modify its surface, insolubility, and recoverability.…”
Section: Introductionmentioning
confidence: 99%
“…40 It is found that the use of nanocatalysts such as magnetic nanoparticles in MCRs leads to high yields, short reaction times, and easy recovery and reuse of the catalyst. [41][42][43][44][45][46][47][48][49] Polyhydroquinoline (PHQ) is a nitrogen-containing organic compound that has a bicyclic structure composed of two hydroquinoline units linked together by a methylene bridge. 50 The synthesis of PHQ derivatives can be modified to produce compounds with specific functional groups and properties, making them useful for a wide range of applications.…”
Section: Introductionmentioning
confidence: 99%
“…MCRs also offer advantages in terms of sustainability and efficiency, as they often require less solvent and generate less waste than traditional synthetic methods 40 . It is found that the use of nanocatalysts such as magnetic nanoparticles in MCRs leads to high yields, short reaction times, and easy recovery and reuse of the catalyst 41–49 …”
Section: Introductionmentioning
confidence: 99%
“…As sustainable and efficient nanocatalysts, MNPs, homogeneous and heterogeneous catalysts in single and composite forms, have emerged as a precious process for meliorating catalytic efficiency and stability. Without an external magnetic field, the MNPs are dispersed in the reaction mixture and make available high surface to the reacting molecules 6 . Due to their excellent characteristics like high atom efficiency, massive surface‐to‐volume ratio, simple handling, facile magnetic separation, high catalytic activities, and high capacity of recyclability, these nanoparticles, with their insoluble nature and magnetic properties, have attracted significant attention and have been widely used, and it has efficiently solved the complicated catalyst separation process 7–13 .…”
Section: Introductionmentioning
confidence: 99%
“…Without an external magnetic field, the MNPs are dispersed in the reaction mixture and make available high surface to the reacting molecules. 6 Due to their excellent characteristics like high atom efficiency, massive surface-to-volume ratio, simple handling, facile magnetic separation, high catalytic activities, and high capacity of recyclability, these nanoparticles, with their insoluble nature and magnetic properties, have attracted significant attention and have been widely used, and it has efficiently solved the complicated catalyst separation process. [7][8][9][10][11][12][13] Magnetic nanoparticles play an essential role in catalysis and biocatalysis owing to their magnetically recoverable and relatively non-toxic nature.…”
Section: Introductionmentioning
confidence: 99%